Transient thermal fatigue crack propagation prediction in a gas turbine component. (December 2021) - Salehnasab, B.; Marzbanrad, J.; Poursaeidi, E.
Highlights: Thermal fatigue crack behaviour of the hot gas path seal of a gas turbine engine under the elastic-perfectly plastic material behaviour is investigated. Circumferential stress during the turbine working cycle causes thermal fatigue cracks initiated and propagated. Transient thermal fatigue crack behaviour can be predicted by the FE model. The Paris and NASGRO model were used to predict the crack propagation behaviour. Abstract: In this study, the thermal fatigue life of the detected crack on the edge of the pinhole of the hot gas path seal of a gas turbine engine under the elastic-perfectly plastic material behaviour is investigated. The component was made by a solid-solution IN625 Ni-based alloy. The non-destructive fluorescent penetration inspection (FPI) method was used to determine the crack position and direction. Stress distribution based on the thermal gradient of the seal was calculated by using a finite element method in accordace with the gas turbine work cycle. The thermal fatigue life was predicted using the ZENCRACK fracture mechanic code. The stress intensity factors (SIFs) were obtained using J-integral and CTOD methods; then, the Paris & NASGRO equations were used to predict fatigue life. Good agreement can be observed between the FE model results and the real cracked components, and the thermal fatigue life under the term of elastic-perfectly plastic material behaviour, in this case, was properly predicted.